Financial burden of gynecologic-cancer survivors associated with attendance in a surveillance program at a tertiary care hospital in Thailand - Suprasert P. (2014)
All gynecologic cancer survivors require a surveillance program for the detection of recurrence and complications after the complete treatment. However, this type of surveillance program might be leading to an unseen burden for the patients. To identify this burden, 200 gynecologic cancer survivors who resided outside of Chiang Mai province were interviewed between November 2010 and February 2011. The mean age of the surveyed patients was 52 years old and most of them were diagnosed with cervical cancer. The mean travelling time was 3.6 hours with a range of one to nine hours and the mean waiting time at the hospital was 5.3 hours. Nearly one-third of the patients required overnight accommodation in Chiang Mai. The mean total cost was 643 baht (60-3,000 baht) and the mean hospital cost was 172 baht. About 44% of the surveyed patients wanted follow up at the local provincial hospital near their abode due to their own convenience. However, more than half of the surveyed patients still wanted to follow up at the tertiary care hospital because of their trust in the medical team. In conclusion, the surveillance program revealed a burden to cancer survivors, especially for the patients who lived a long distance away from the tertiary care hospital province.